2020
DOI: 10.1101/2020.11.27.401489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual motion processing recruits regions selective for auditory motion in early deaf individuals

Abstract: In early deaf individuals, the auditory deprived temporal brain regions become engaged in visual processing. In our study we tested further the hypothesis that intrinsic functional specialization guides the expression of cross-modal responses in the deprived auditory cortex. We used functional MRI to characterize the brain response to horizontal, radial and stochastic visual motion in early deaf and hearing individuals matched for the use of oral or sign language. Visual motion showed enhanced response in the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Several studies of crossmodal plasticity propose a preservation of function in auditory areas, where these regions maintain their original computation but adapt to respond to a different sensory input (Lomber et al, 2010; Cardin et al, 2013; Bola et al, 2017; Benetti et al, 2017, 2021). Other studies have suggested that sensory-deprived auditory regions are involved in higher-order cognitive functions, suggesting a functional change (see for a review Cardin et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of crossmodal plasticity propose a preservation of function in auditory areas, where these regions maintain their original computation but adapt to respond to a different sensory input (Lomber et al, 2010; Cardin et al, 2013; Bola et al, 2017; Benetti et al, 2017, 2021). Other studies have suggested that sensory-deprived auditory regions are involved in higher-order cognitive functions, suggesting a functional change (see for a review Cardin et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Our study extends these findings to show that metamodal engagement is possible in auditory cortex as well. To our knowledge, metamodal engagement of auditory cortex has been limited to posterior auditory association cortex (pSTS) and has only been found in congenitally deaf but not hearing individuals (Benetti et al, 2017, 2020; Bola et al, 2017; Twomey et al, 2017). Furthermore, these studies did not find evidence of metamodal engagement in neurotypical individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A prime example of this process is reading, which is initially thought to recruit auditory speech processing pathways through grapheme-to-phoneme conversion (Pugh et al, 2001), and the same idea has given rise to promising therapeutic applications such as sensory substitution devices (SSDs, which, for instance enable processing of visual information in blind individuals by translating camera input to acoustic stimuli (Bach-y-Rita and Kercel, 2003; Meijer, 1992). Yet, other studies (Benetti et al, 2017, 2020; Bola et al, 2017; Fairhall et al, 2017; Mattioni et al, 2020; Pietrini et al, 2004; Twomey et al, 2017; Vetter et al, 2020) have failed to find or have found far less robust evidence of cross-modal engagement in neurotypical subjects, raising the critical question of the conditions under which a particular sensory area can be successfully recruited for “metamodal” processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review will focus on studies on crossmodal plasticity, which concerns changes in areas that are typically associated with a modality that is not received and processed. Examples are higher activity in auditory areas in deaf compared to hearing individuals during visual stimulation (Finney et al, 2001;Fine et al, 2005;Benetti et al, 2021) and tactile stimulation (Karns et al, 2012;Zimmermann et al, 2021), or activity in visual areas of blind individuals who are listening to speech (Bedny et al, 2011). Benetti et al (2021) presented patterns of moving dots and observed significantly stronger activation in typical auditory areas in early deaf participants compared to hearing signers and non-signers.…”
Section: Introductionmentioning
confidence: 99%